Nexus of ecosystem service-human health-natural resources: The nature-based solutions for urban PM2.5 pollution. (April 2023) - Chen, Han-Shi; Lin, Ying-Chen; Chiueh, Pei-Te
Highlights: Nexus of nature and human society were analyzed via the proposed research framework. PM2.5 regulation services and their benefits for human health were both evaluated. Urban green can reduce the health incidence of premature death and certain diseases. The suitable locations for the nature-based solutions in Taipei City were identified. The results can be the guideline for future urban green infrastructure planning. Abstract: With modern industrialization and urbanization, air pollution has become a significant environmental problem in urban areas. The effective removal of air pollutants is crucial for improving air quality, maintaining human health, and achieving human well-being. As the most densely populated city in Taiwan, Taipei City faces a severe fine particulate matter (PM2.5 ) exposure problem. This study proposes a conceptual framework in response to urban PM2.5 pollution that adversely affects human health. The PM2.5 removal capacity provided by urban vegetation within Taipei City was first quantified, and its public health benefits were then evaluated. The optimal locations for different nature-based solutions (NBS) were also identified, which could be applied when forming urban PM2.5 pollution mitigation policies. The results revealed that the urban vegetation of Taipei City in 2016 contributed to reducing the health incidence change of premature death and certain diseases, equated monetarily to New Taiwan Dollar (NT) 9.43E+08. In addition, as one of the four evaluated NBS, direct vertical greening presented with the highest benefit-cost ratio for Taipei City. Spatial mappings of the different NBS locations could guide the government in planning sustainable urban green infrastructure in the future. Graphical abstract: Image, graphical abstract